Consistent Geometric Patterns Observed in Three-Dimensional Displacement of Nationwide GNSS Stations in Japan - Junichi Susaki (IEEE Access)
This study explored the possibility of using currently available data to forecast when and where a large earthquake could occur in the near future. Such forecasts require measurements and understanding of past and current three-dimensional (3D) displacement patterns. We analyzed the geometric patterns of 3D displacement using coordinate data from over 1,300 global navigation satellite system stations in Japan. We found that the monthly displacement velocities of a station were on a single flat plane, although a significantly large earthquake had occurred, and the normal planes of all stations were on a single quadratic curve surface. Moreover, the sum of the absolute differences in 15-d velocities indicated a significant displacement over a wide area after the occurrence of a large earthquake.